Optimizing Early Recognition and Management of Sepsis Secondary to Pneumonia: A Literature Review - Adhyaksa, I Wayan Pande (Respiratory Science, 2025)
Sepsis, a life-threatening organ dysfunction caused by a dysregulated host response to infection, frequently complicates pneumonia, a leading global cause of morbidity and mortality. This review synthesizes current evidence on optimizing early recognition and management of sepsis secondary to pneumonia, highlighting critical diagnostic and therapeutic strategies. Streptococcus pneumoniae remains the predominant pathogen in community-acquired pneumonia (CAP), though antimicrobial resistance and atypical organisms pose growing challenges. Key risk factors include comorbidities (e.g., renal/liver disease, diabetes), immunosuppression, and socioeconomic determinants. Early diagnosis combines clinical assessment (e.g., SOFA, qSOFA scores) with biomarkers like procalcitonin, lactate, and neutrophil-to-lymphocyte ratio (NLR). Innovative tools, such as AI-driven analysis of blood count data, show promise for rapid sepsis detection. The cornerstone of management is the "1-hour bundle": immediate broad-spectrum antibiotics (tailored to local resistance patterns), fluid resuscitation with crystalloids, and vasopressors for refractory hypotension. Antibiotic selection must account for pathogen profiles, with macrolides or fluoroquinolones recommended for severe CAP. Fluid balance is critical to avoid pulmonary edema, while organ support (e.g., mechanical ventilation) is often required for respiratory failure. Despite therapeutic advances, sepsis mortality remains high (24–65% in Indonesia), driven by delays in treatment and comorbid conditions. Survivors frequently face long-term physical and cognitive impairments, necessitating comprehensive rehabilitation. Future efforts should prioritize rapid diagnostics, personalized therapy, and post-sepsis care to improve outcomes. This review underscores the importance of early, protocol-driven interventions to mitigate the global burden of sepsis complicating pneumonia.